Green synthesis of methoxy-poly(ethylene glycol)-block-poly(l-lactide-co-glycolide) copolymer using zinc proline as a biocompatible initiator for irinotecan delivery to colon cancer in vivo. (18th November 2020) - Giram, Prabhanjan S.; Wang, Julie Tzu-Wen; Walters, Adam A.; Rade, Priyanka P.; Akhtar, Muhammad; Han, Shunping; Faruqu, Farid N.; Abdel-Bar, Hend M.; Garnaik, Baijayantimala; Al-Jamal, Khuloud T.
Abstract : Green synthesis of mPEG–PLGA and nanoformulation for delivery of irinotecan to colon cancer. Abstract : Poly(lactic- co -glycolic acid) (PLGA) is the most commonly described biocompatible copolymer used in biomedical applications. In this work, a green synthetic approach based on the biocompatible zinc proline complex, as an initiator for PLGA synthesis, is reported for the first time for the synthesis of methoxy-poly(ethylene glycol)- block -poly(l -lactic- co -glycolic acid) (mPEG–PLGA). mPEG–PLGA with controlled molecular weight and narrow polydispersity was synthesised. Its potential for delivery of irinotecan (Ir), a poorly water-soluble chemotherapeutic drug used for the treatment of colon and pancreatic cancer, was studied. Nanoparticles of controlled size (140–160 nm), surface charge (∼−10 mV), release properties and cytotoxicity against CT-26 (colon) and BxPC-3 (pancreatic) cancer cells, were prepared. Tumor accumulation was confirmed by optical imaging of fluorescently labelled nanoparticles. Unlike Tween® 80 coated NP-Ir, the Pluronic® F-127 coated NP-Ir exhibits significant tumor growth delay compared to untreated and blank formulation treated groups in the CT-26 subcutaneous tumor model, after 4 treatments of 30 mg irinotecan per kg dose. Overall, this proof-of-concept study demonstrates that the newly synthesized copolymer, via a green route, is proven to be nontoxic, requires fewer purification steps and has potential applications in drug delivery.